ANALYSIS OF EXPORT POTENTIAL AND THE ROLE OF RUSSIA IN THE GLOBAL COAL MARKET - Peter A. Apukhtin (Статистика и экономика, 2016)
The role of Russia in the global coal market, as well as meaning of exports of coal production for the country has been increased during the last decade. Growth of competition on the world market has become a dangerous trend, Russia facing the leading mining countries. The major structural changes in the world coal trade during periods of active growth in coal exports from Russia in 2000-2011 years have been analyzed. The role of and place of Russia has been revealed in the global market and possibilities of increasing competitiveness.